Compressed Biogas-Diesel Dual-Fuel Engine Optimization Study for Ultralow Emission - GÜL, MEHMET ZAFER; YILMAZ, MUSTAFA (SAGE PUBLICATIONS LTD, 2014)
The aim of this study is to find out the optimum operating conditions in a diesel engine fueled with compressed biogas (CBG) and pilot diesel dual-fuel. One-dimensional (1D) and three-dimensional (3D) computational fluid dynamics (CFD) code and multiobjective optimization code were employed to investigate the influence of CBG-diesel dual-fuel combustion performance and exhaust emissions on a diesel engine. In this paper, 1D engine code and multiobjective optimization code were coupled and evaluated about 15000 cases to define the proper boundary conditions. In addition, selected single diesel fuel (dodecane) and dual-fuel (CBG-diesel) combustion modes were modeled to compare the engine performances and exhaust emission characteristics by using CFD code under various operating conditions. In optimization study, start of pilot diesel fuel injection, CBG-diesel flow rate, and engine speed were optimized and selected cases were compared using CFD code. CBG and diesel fuels were defined as leading reactants using user defined code. The results showed that significantly lower NOx emissions were emitted under dual-fuel operation for all cases compared to single-fuel mode at all engine load conditions.
Keywords: MODELS